Effect of injection pressure and nozzle strategy optimization for the performance improvement on CI engine fuelled with diesel and co-gasified biomass producer gas: A diesel-RK and RSM-based approach - Prajapati L.K.; Tirkey J.V. (My University, 2025)
Gasification can offer a sustainable solution to energy demands by converting solid biomass into gaseous fuels for power generation. But there is still a research gap to improve the gasifier-engine performance through parametric setting and optimization. Therefore, this study explores the co-gasification of coconut shell and briquetted sugarcane bagasse to produce producer-gas for CI engine. The novelty is to analyse the impact of number of nozzles, injection pressure, and engine load on engine performance using Diesel-RK modeling. The simulated results were validated with experimental pressure-crank angle variation, observed high R2 (0.995) value of accuracy. The Response Surface Methodology (RSM) was used to optimize the brake power (BP), brake-thermal efficacy (BTE), brake-specific fuel consumption (BSFC), particulate matter (PM), CO₂, and NOₓ emissions. The key findings were obtained as BTE of 31.3 %, and the optimal input conditions were five nozzles, 210.54 bar injection pressure, and 99.47 % load. The resulting optimal output values BP, BTE, BSFC, CO₂, PM, and NOₓ were estimated as 2.919 kW, 31.145 %, 0.506 kg/kWh, 0.89 g/kWh, 957.68 g/kWh, and 11.81 g/kWh correspondingly, with an overall desirability score of 0.871, indicating favorable results across responses. The findings highlight co-gasification's potential to improve efficiency, lower emissions, and support sustainable energy. © 2025 The Institution of Chemical Engineers